Unreading Borges's Labyrinths - Lawrence R. Schehr (Studies in 20th & 21st Century Literature, 1986)
Borges's stories often valorize the figures of text and labyrinth, and, in "The Garden of Forking Paths," an identity is posited between them. This identity is the means to deconstructing the story and, at the same time, for refusing both structuralist and metaphysical readings of the work. The text of the story gradually subsumes the world it seeks to represent under and within an all-encompassing textuality without origin and without any clearly delimited meaning except absence, the destruction of meaning, death. The solution of the labyrinth is its dissolution, that is, the deconstruction of the text. This easily thematizable deconstruction is actually a far more radical and subtle deconstruction of the text as structure or "meaning." Intertextuality and fragmentation undo the work and underline what amounts to a series of transgressions. These transgressions, that is, the text itself, are attempts to fill the void of the signified with signifier. And these transgressions, read, understood, and thereby iterated by the reader, are the signs of the deferred desire central to the work, its fundamental and radical difference.
Keywords: Borges; labyrinth; The Garden of the Forking Paths; identity; deconstruction; structuralist readings; metaphysical readings; textuality; meaning; death; fragmentation; signified; sign; signifier; difference; Argentine literature